Strategi Pembelajaran Bahasa Inggris Interaktif Berbasis Media Digital Bagi Siswa Sekolah Menengah Atas - Putri, Miranti Eka; Ilyas, Muhammad; Ramadan, Zaka Hadikusuma; Fatricia, Niken; Ermalisa, Suci (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid development of digital technology has encouraged the need for innovation in the learning process, including English language instruction at the secondary school level. However, English learning is still often dominated by conventional teaching methods that are less effective in enhancing students’ motivation and language skills. Therefore, the integration of interactive digital media is considered a potential alternative to create a more engaging and effective learning environment. This Community Service Program (PKM) aims to improve the English learning skills of students at SMA IT Imam Syafi’i Cendikia Pekanbaru through the use of interactive digital media. The implementation methods included material presentation, demonstrations of digital learning applications, hands-on practice, and continuous assistance conducted both offline and online. The program was carried out in three training sessions focusing on the development of listening, speaking, and vocabulary enrichment skills using digital platforms such as learning applications, interactive videos, and technology-based exercises. The results indicate that the use of interactive digital media significantly increased students’ learning motivation, with most participants stating that the learning materials were easy to understand. In addition, students demonstrated increased activeness and independence in the learning process. Therefore, interactive digital media can be considered an effective alternative learning strategy to support English language learning in schools